The Effect of Giving Krispi Potato Skin on Increasing Hemoglobin Levels in Adolescent Girls at Salafiyah Syafi'iyah Islamic Boarding School Sukorejo Situbondo - Ifa Nurhasanah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction: An adolescent is someone who experiences rapid growth and development. Not infrequently, information that says that adolescents often experience several diseases, especially anemia. anemia is characterized by Hb levels below normal. Usually those who often experience anemia are adolescent girls, therefore it is necessary to prevent and overcome anemia by increasing Hb levels. Objective: the purpose of this study was to determine the effect of giving crispy potato skins on increasing hemoglobin levels in adolescent girls at the Salafiyah Syafi'iyah Islamic Boarding School in Sukorejo Situbondo. Methods: the method used in this study is a pre-experiment one group test, conducted on adolescent girls aged 13-22 years as many as 25 people. Result: the results of this study are independent variables, namely age (0.227), knowledge (0.517) and provision of potato skins (0.999) have no effect on increasing Hb levels. Conclusions: the conclusion of this study is to minimize the level of error when conducting research so that the results obtained are maximized and in accordance with the desired research objectives.